Rene, ADPKD e COVID-19: il doppio ruolo della fragilità renale. - Maria Teresa Sciarrone Alibrandi; Marta Vespa (AboutScience Srl, 2020)
The Corona Virus Disease 19 (COVID19) is an infectious disease caused by SARS - CoV - 2 (Severe Acute Respiratory Syndrome Coronavirus 2). By now, the pandemic has already led 318000 people to their death and our knowledge of this pathogen is still in its infancy. What we know so far is that older patients suffering from different comorbidities, such as heart failure, COPD and tumors, are keener to develop severe complications from which they might perish. The role of chronic kidney disease is still not clear, though. What we do know is that CKD patients are more susceptible to infections, both viral and bacterial, compared to the main population. It has been recently highlighted that the immune response might be the real cause of damage in the lung tissues and not just the virus itself, therefore, the better the immune response, the greater the damage. Quite paradoxically, being chronically renal impaired and suffering from a delayed T-Cell response might actually be beneficial, avoiding a massive inflammatory reaction followed by SARS. According to a recent survey led by the SIN (Italian Society of Nephrology), only 2.8% of COVID patients is under hemodialysis treatment. Unfortunately, we do not have more detailed data on every single specific form of CKD. For instance, there is no clear relation between COVID19 an ADPKD.  What might be inferred is the following: COVID uses the ACE2 receptors on cell membranes to "lock on " its target. It is a well-established fact that the RAAS is more active in ADPKD patients, whether it is a matter of hyper activation or hyper-expression of ACE2 receptors it's not clear. Also, the fact that these patients are usually on drug treatment with an ACE Inhibitor or an ARB might have some implications that are definitely worth analyzing.